New insights into potential risk factors and associations in genital lichen sclerosus: Data from a multicentre Italian study on 729 consecutive cases. (12th August 2016) - Virgili, A.; Borghi, A.; Cazzaniga, S.; Di Landro, A.; Naldi, L.; Minghetti, S.; Verrone, A.; Stroppiana, E.; Caproni, M.; Nasca, M.R.; D'Antuono, A.; Papini, M.; et al.
Abstract: Background: Limited data are available on risk factors associated with lichen sclerosus and no data are available on gender differences in genital lichen sclerosus (GLS). Objective: This multicentre study aimed at identifying potential risk factors for GLS, through data collection from a large, mixed‐sex sample of patients comparing gender‐related differences in relation to data from the general population. Methods: This was a cross‐sectional study on 729 subjects (53.8% females, 46.2% males) affected with GLS, consecutively observed within a network of 15 Italian dermatology units. The following information was collected: demographic data, anthropometric measures, comorbidities, family history of LS, clinical features and symptoms related to GLS. Results: Overweight and obesity, blood hypertension, hypothyroidism and an educational attainment equal or above upper secondary school level were more frequent among the study patients than among the general Italian population. Moreover, a family history of GLS was reported more frequently than expected among GLS patients. These factors were similar in males and females. The disease tended to occur later in females than in males. Conclusions: Our findings suggest that metabolic factors, and possibly a sedentary lifestyle, may play a role in GLS pathogenesis in genetically predisposed patients, and that risk profile is similar in males and females despite some difference in the onset of symptoms.